2014
DOI: 10.1002/elsc.201400159
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced release of tanshinones and phenolics by nonionic surfactants from Salvia miltiorrhiza hairy roots

Abstract: Practical applicationSalvia miltiorrhiza root or Danshen is a well-known and valuable Chinese herb. Danshen contains two major classes of bioactive constituents, diterpenoid tanshinones and phenolic acids. These intracellular metabolite products are mainly retained within the S. miltiorrhiza hairy roots. In this study, several non-ionic surfactants were applied as membrane permeabilization agents to the S. miltiorrhiza hairy root culture, some of which were found effective to stimulate the release of tanshinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The production of phenolic compounds is the main goal of the vast majority of those studies (Andarwulan and Shetty, 1999;Lozovaya et al, 2000;Santos-Gomes et al, 2003;Gális et al, 2004;Lozovaya et al, 2006;Kouakou et al, 2007;Bairu et al, 2011;Cui et al, 2011;Krzyzanowska et al, 2011;Palacio et al, 2012;Szopa et al, 2013;Siu et al, 2014;Szopa and Ekiert, 2014;Yildirim and Turker, 2014). However, some of them are also focused on the study of the extract's bioactive properties, such as antioxidant (Grzegorczyk et al, 2007;Hakkim et al, 2007;Kovatcheva-Apostolova et al, 2008;Hussein et al, 2010;Amoo et al, 2012;Giri et al, 2012;Khateeb et al, 2012; 16 Barros et al, 2013;Bhagya and Chandrashekar, 2013;Cheniany et al, 2013;Madhu, 2013;Goyali et al, 2014;Lugato et al, 2014;Piątczak et al, 2014;Valdez-Tapia et al, 2014), antimicrobial (Hussein et al, 2010;Ncube te al., 2011;Zhao et al, 2011;Khateeb et al, 2012) and cytotoxic (Skorić et al, 2012) activities.…”
Section: Production Of Phenolic Compounds Through Plant Tissue Culturmentioning
confidence: 99%
“…The production of phenolic compounds is the main goal of the vast majority of those studies (Andarwulan and Shetty, 1999;Lozovaya et al, 2000;Santos-Gomes et al, 2003;Gális et al, 2004;Lozovaya et al, 2006;Kouakou et al, 2007;Bairu et al, 2011;Cui et al, 2011;Krzyzanowska et al, 2011;Palacio et al, 2012;Szopa et al, 2013;Siu et al, 2014;Szopa and Ekiert, 2014;Yildirim and Turker, 2014). However, some of them are also focused on the study of the extract's bioactive properties, such as antioxidant (Grzegorczyk et al, 2007;Hakkim et al, 2007;Kovatcheva-Apostolova et al, 2008;Hussein et al, 2010;Amoo et al, 2012;Giri et al, 2012;Khateeb et al, 2012; 16 Barros et al, 2013;Bhagya and Chandrashekar, 2013;Cheniany et al, 2013;Madhu, 2013;Goyali et al, 2014;Lugato et al, 2014;Piątczak et al, 2014;Valdez-Tapia et al, 2014), antimicrobial (Hussein et al, 2010;Ncube te al., 2011;Zhao et al, 2011;Khateeb et al, 2012) and cytotoxic (Skorić et al, 2012) activities.…”
Section: Production Of Phenolic Compounds Through Plant Tissue Culturmentioning
confidence: 99%
“…Meanwhile, the results showed that all six strains were able to increase the contents of RA and SAB in the hairy roots of S. miltiorrhiza . The increase rate of phenolic acids production induced by strain LNHR13 (the best strain) was less significantly than that by some signal molecules, such as ethylene and SA , whereas better than other elicitors, such as heavy metal salts (Ag + ) , nonionic surfactants (Tween 20 and Triton X‐100) and yeast extract . Above all, the evidence about phenolic acids content promoted by biotic elicitors is rarely available, and even most of the biotic elicitors (both live microbes and constituents of microbial cells) inhibit the biosynthesis of phenolic acids .…”
Section: Discussionmentioning
confidence: 99%
“…Salvia miltiorrhiza Bunge (Lamiaceae), commonly known as Danshen, is an important herb in China . Its rhizomes, having been widely used in the treatment of cerebrovascular and cardiovascular diseases in China as well as other countries, contain two types of bioactive substances, namely, phenolic acids and tanshinones .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue culture provided the first bioactive components of S. miltiorrhiza in the 1980s. Today, the yield of secondary metabolism has been remarkably improved by polyploid induction, callus culture [64], transformed cell suspension culture and hairy root culture [5].…”
Section: Plant Cell and Tissue Culturesmentioning
confidence: 99%